1).
2.
3.
1.Lgx=2+lg3-lg5
Lgx=2lg10+lg3/5
Lgx=lg100*3/5
Lgx=lg60
x=60
2.log2X+log8X=8
log2X+1/3*log2X=8
log2X*X^1/3=8
x^4/3=2^8
x=2^6
x=64
3.log3(1-2x)=1
1-2x=3
2x=-2
x=-1
1).![lg x=2+lg_3-lg_5;\\ x0;\\ lg x=lg 10^2+lg_3-lg_5;\\ lg x=lg 100+lg_3-lg_5;\\ lg x=lg \frac{100*3}{5};\\ lg x=lg 60;\\ x=60](/tpl/images/0075/0162/47992.png)
2.![log_2 x+log_8 x=8;\\ x0;\\ log_2 x+log_{2^3} x=8;\\ log_2 x+\frrac{1}{3} log_2 x=8;\\ 3log_2 x+log_2 x=24;\\ 4log_2 x=24;\\ log_2 x=24:4;\\ log_2 x=6;\\ x=2^6;\\ x=64](/tpl/images/0075/0162/35bf4.png)
3.![log_3 (1-2x)=1;\\ 1-2x0;12x;0.5x;\\ x<0.5;\\ 1-2x=3^1;\\ 1-2x=3;\\ 2x=1-3;\\ 2x=-2;\\ x=-2:2;\\ x=-1](/tpl/images/0075/0162/13204.png)
1.Lgx=2+lg3-lg5
Lgx=2lg10+lg3/5
Lgx=lg100*3/5
Lgx=lg60
x=60
2.log2X+log8X=8
log2X+1/3*log2X=8
log2X*X^1/3=8
x^4/3=2^8
x=2^6
x=64
3.log3(1-2x)=1
1-2x=3
2x=-2
x=-1